ANALISIS PEMASARAN PRODUK ROTAN OLAHAN DI KOTA BINJAI - Pardamean Tampubolon; Irawati Azhar; Tito Sucipto (Program studi Kehutanan USU, 2015)
Utilization of non timber forest products, especially rattan gives a positive impact on industrial development in Indonesia. This study aims to determine the type and price of raw materials of rattan and rattan products processed were traded, and analyze the marketing flow of rattan product processed in Binjai of raw materials derived from Langkat. Data retrieved through interviews with intermediaries rattan craftsmen and traders, and tabulated, then calculated using the formula of marketing margins and profit margins are then analyzed. Rattan species that dominate in the industry, namely sega (Calamus caesius Blume) and getah (Daemonorops angustifolia Mart) and the type of rattan genera Calamus and Daemonorops be priced between Rp.3.000-Rp.20.000 per stem or per kg. Processed rattan products are tables, chairs, baskets, hood serving, place parcel rattan, wicker mirror with a selling price of between Rp.8.000-Rp.400.000 per unit. Based on the R/C ratio of the products in the rattan industry Aslinda, production of wicker basket viable and economically beneficial to the R/C ratio > 1 of 100 units of the product. There are three (3) types of marketing flow in Binjai, that is 1). The craftsmen is directly to consumer, 2). The craftsmen to store/retailers who will resell it to consumers and 3). The craftsmen and also seller to the consumer.Keywords : rattan, rattan products, marketing analysis, R/C ratio